RANCANG BANGUN UNIPOLAR PWM UNTUK PENGENDALIAN RANGKAIAN H-BRIDGE MENGGUNAKAN OPERATIONAL AMPLIFIER - Asmar Asmar (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
Unipolar PWM control technique carried out by comparing triangular wave with two control voltages. The resulting pulses are used to control H-Bridge circuit. The technique can be done by using the functions of the operational amplifier. There are three main circuits needed is a triangular wave circuit, voltage control circuit, and a comparator circuit. With proper adjustment between the triangular waves and voltage control, voltage regulation will be obtained smooth.